2016
DOI: 10.1097/tp.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Preemptive Kidney Transplantation in the United States

Abstract: BACKGROUND Preemptive kidney transplantation (preKT) is associated with higher patient survival, improved quality of life, and lower costs. However, only a minority of patients receives preKT. The aim of this study was to examine changes over the past decade in rates of preKT, focusing on living donor kidney transplantation (LDKT) and specifically recipients who underwent kidney transplantation within one year of initiating dialysis. METHODS Using United Network of Organ Sharing data, we examined retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 23 publications
6
63
0
4
Order By: Relevance
“…[14] This is a potential reflection of a loss of private contracts after a LP higher rates of LDKT among recipient with private insurance as the primary payer. [26, 27]…”
Section: Unitended Consequences and Disincentivesmentioning
confidence: 99%
“…[14] This is a potential reflection of a loss of private contracts after a LP higher rates of LDKT among recipient with private insurance as the primary payer. [26, 27]…”
Section: Unitended Consequences and Disincentivesmentioning
confidence: 99%
“…Studies have identified race and ethnicity, body mass index, health insurance, gender, age, community risk factors, and primary cause of kidney disease as factors associated with time to placement on a waiting list for transplantation . Many of these factors are also associated with preemptive transplantation, which continues to occur in a small minority of transplants in the United States . Factors that are associated with access to repeat transplantation may be unique as compared to patients without a prior transplant, given prior navigation of processes to acquire a transplant and prior qualification as a viable transplant candidate.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Many of these factors are also associated with preemptive transplantation, which continues to occur in a small minority of transplants in the United States. 13,14 Factors that are associated with access to repeat transplantation may be unique as compared to patients without a prior transplant, given prior navigation of processes to acquire a transplant and prior qualification as a viable transplant candidate. In addition, the duration, complications, and reasons for graft failure from initial transplantation may predispose patients' willingness and viability for a repeat transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only 11% of deceased donor kidney transplants are performed preemptively, and only 2.5% of all patients with end-stage renal disease undergo preKT. 5,10,11 Non-ideal renal allografts, previously designated as extended criteria donor (ECD) kidneys, represent 1 opportunity for increasing access to earlier and potentially preemptive transplantation in older patients.…”
Section: Introductionmentioning
confidence: 99%